Why Isn't South Africa Growing Faster? Microeconomic Evidence from a Firm Survey - Clarke, George; Habyarimana, James; Kaplan, David; Ramachandran, Vijaya (2012)
The investment levels in South Africa have remained relatively low despite an overall picture of economic stability and good governance. This analysis looks at South Africa's investment climate, using data from an Investment Climate Survey (ICS) of over 800 firms conducted by the Department of Trade and Industry and the World Bank. It suggests that exchange rate instability and the cost of crime may be deterrents to investment. But more importantly, labour regulations may be discouraging firms from entering labour-intensive areas. Labour costs are also high, especially for skilled workers. Efforts to improve worker skills are crucial for raising human capital levels and reducing the cost of skilled labour.